Imaging Arm Regeneration: Label-Free Multiphoton Microscopy to Dissect the Process in Octopus vulgaris - Imperadore, Pamela; Galli, Roberta; Winterhalder, Martin J.; Zumbusch, Andreas; Uckermann, Ortrud (Frontiers in Cell and Developmental Biology, 2022)
Cephalopod mollusks are endowed with an impressive range of features that have captured the attention of scientists from different fields, the imaginations of artists, and the interests of the public. The ability to spontaneously regrow lost or damaged structures quickly and functionally is among one of the most notable peculiarities that cephalopods possess. Microscopical imaging techniques represent useful tools for investigating the regenerative processes in several species, from invertebrates to mammals. However, these techniques have had limited use in cephalopods mainly due to the paucity of specific and commercially available markers. In addition, the commonly used immunohistochemical staining methods provides data that are specific to the antigens studied. New microscopical methods were recently applied to vertebrates to investigate regenerative events. Among them, multiphoton microscopy appears promising. For instance, it does not depend on species-related epitopes, taking advantage of the specific characteristics of tissues and allowing for its use in a species-independent way. Here we illustrate the results obtained by applying this label-free imaging technique to the injured arm of Octopus vulgaris, a complex structure often subject to injury in the wild. This approach allowed for the characterization of the entire tissue arm architecture (muscular layers, nerve component, connective tissues, etc.) and elements usually hardly detectable (such as vessels, hemocytes and chromatophores). More importantly, it also provided morpho-chemical information which helped in deciphering the regenerative phases after damage, from healing to complete arm regrowth, thereby appearing promising for regenerative studies in cephalopods and other non-model species.